Farmer-friendly ivy gourd - Maurya, K R (Indian Horticulture, 2019)
Ivy gourd is one of the minor cucurbits of major importance from regular and more income generation point of view. An yield of 300-400 q/ha is harvested which gives a gross return of `2,80,000 if fruits are sold at a minimum rate of `800/q. Total cost of cultivation comes to `80,000/ha, including cost of bower of wire net. Thus, a net profit of `2.0 lakh/ha is very easily obtained.